PENGARUH MEDIA MANIPULATIF TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS PADA PEMBELAJARAN MATEMATIKA KELAS V SD - Bela, Acytri; Bistari, Bistari; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to analyze the effect of using manipulative media on the ability of mathematical representation of students in flat wake symmetry material in class V Pontianak City 66 State Elementary School. The method used is the experimental method, a quasi experimental design with nonequivalent control group design. The population and sample in this study were all fifth grade students of Pontianak City 66 State Elementary School. The data collection tool used in the form of an Essay test consisted of 5 questions. Based on data analysis, the average post-test results of the experimental class were 82.63 while the average post-test results of the control class were 59.15. The results of the t test are obtained tcount 9.0298 and t table Î± = 5% (with dk = 33 + 32 - 2 = 63) of 1.9990, which means tcount (9.1031)> t table (1.9990), then the hypothesis alternative (Ha) is accepted. From the results of the calculation of the effect size (ES) ES obtained was 2.5 (high criteria). It can be concluded that manipulative media have a good influence on the mathematical representation ability of students in class V of Pontianak City 66 State Elementary School.Â Keywords: Flat Symmetry, Manipulative Media, Mathematical Representation Ability.